Mutations of the Membrane-Bound Disulfide Reductase DsbD That Block Electron Transfer Steps from Cytoplasm to Periplasm in Escherichia coli - Cho, Seung-Hyun (American Society for Microbiology, 2006)
The cytoplasmic membrane protein DsbD keeps the periplasmic disulfide isomerase DsbC reduced, using the cytoplasmic reducing power of thioredoxin. DsbD contains three domains, each containing two reactive cysteines. One membrane-embedded domain, DsbDβ, transfers electrons from thioredoxin to the carboxy-terminal thioredoxin-like periplasmic domain DsbDγ. To evaluate the role of conserved amino acid residues in DsbDβ in the electron transfer process, we substituted alanines for each of 19 conserved amino acid residues and assessed the in vivo redox states of DsbC and DsbD. The mutant DsbDs of 11 mutants which caused defects in DsbC reduction showed relatively oxidized redox states. To analyze the redox state of each DsbD domain, we constructed a thrombin-cleavable DsbD (DsbD(TH)) from which we could generate all three domains as separate polypeptide chains by thrombin treatment in vitro. We divided the mutants with strong defects into two classes. The first mutant class consists of mutant DsbDβ proteins that cannot receive electrons from cytoplasmic thioredoxin, resulting in a DsbD that has all six of its cysteines disulfide bonded. The second mutant class represents proteins in which the transfer of electrons from DsbDβ to DsbDγ appears to be blocked. This class includes the mutant with the most clear-cut defect, P284A. We relate the properties of the mutants to the positions of the amino acids in the structure of DsbD and discuss mechanisms that would interfere with the electron transfer process.